Relationship between Personal Hygiene Knowledge Level and Vulva Hygiene Behavior During Menstruation in Adolescent Girls - Istikhomah, Indah; Putri, Dwi Khalisa; Wahyuningsih, Erma Noor (Journal of Midwifery and Nursing, 2025)
Background: Personal hygiene is an individual's effort to maintain and care for personal hygiene for personal comfort. Genital area hygiene, especially during menstruation, is often neglected by women. During menstruation, blood and sweat can stick to the vulva, which causes moisture in the genital area. Knowledge about personal hygiene affects individual hygiene behavior. Objective: The study aims to evaluate knowledge about personal hygiene and vulva hygiene behavior during menstruation in female adolescents. Method: Using a cross-sectional design with a sample of 60 respondents with a total sampling technique. The focus of the study was female adolescents in grades VIII and IX of MTS AL-Ihsan. The research instrument was a questionnaire that measured behavior related to personal hygiene during menstruation. Research Results: Of the total 60 respondents, 27 respondents (45%) had poor knowledge, while 15 respondents (25%) had sufficient knowledge, and 18 respondents (30%) had good knowledge. Regarding behavior, 28 respondents (46.7%) showed poor behavior, 23 respondents (38.3%) had sufficient behavior, and 9 respondents (15%) showed good behavior. The results of the Chi-square statistical analysis (Pearson Chi-square) showed a value of ?² = 35.478 with asymp.sig (p) = 0.001 <0.05, which means the results are significant, so the null hypothesis is rejected and the alternative hypothesis is accepted. This clarifies the connection between knowledge and personal hygiene behaviors. Conclusion: This study found that there are still many female adolescents who have insufficient knowledge, namely 27 respondents (45%), and poor behavior is also high, namely 28 out of 60 respondents (46.7%). Healthcare workers need to stay more updated in improving students' knowledge, which can be done through media in disseminating information about vulva hygiene during menstruation.